2018
DOI: 10.1590/1807-1929/agriambi.v22n2p101-106
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus fertilization of sunflower crop in alkaline Cambisol

Abstract: A B S T R A C TSunflower is a crop that has aroused the interest of farmers because of its adaptability to wide climatic conditions and for its use in biodiesel production. However, there are only a few studies on sunflower fertilization in alkaline soils. This study aimed to evaluate nitrogen (N) and phosphorus (P) fertilization in sunflower (Helianthus annuus L.) cultivated in alkaline soil. A field experiment was carried out in Baraúnas-RN, Brazil, in a Haplic Cambisol derived from calcareous rock, where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(11 reference statements)
0
1
0
2
Order By: Relevance
“…O fósforo é um elemento químico essencial para o crescimento e desenvolvimento das plantas, sendo constituinte de moléculas importantes no metabolismo e estrutura das células [21]. Como a maioria dos solos brasileiros tem baixa disponibilidade de fósforo, tem-se observado resposta positiva da cultura do girassol à adubação fosfatada [5][6][7]. No presente trabalho verificou-se que o MAP tratado com polímeros apresentou melhor desempenho que o ST sem polímeros em relação à altura média de plantas das variedades Embrapa 122 e IAC Uruguai.…”
Section: Variedadesunclassified
See 1 more Smart Citation
“…O fósforo é um elemento químico essencial para o crescimento e desenvolvimento das plantas, sendo constituinte de moléculas importantes no metabolismo e estrutura das células [21]. Como a maioria dos solos brasileiros tem baixa disponibilidade de fósforo, tem-se observado resposta positiva da cultura do girassol à adubação fosfatada [5][6][7]. No presente trabalho verificou-se que o MAP tratado com polímeros apresentou melhor desempenho que o ST sem polímeros em relação à altura média de plantas das variedades Embrapa 122 e IAC Uruguai.…”
Section: Variedadesunclassified
“…Nas principais regiões produtoras de grãos do Brasil, a possibilidade de cultivo do girassol durante o ano todo é possível em função da baixa sensibilidade fotoperiódica da planta, porém, cuidados devem ser destinados às limitações na disponibilidade de fósforo (P) no início do ciclo vegetativo, que podem resultar em restrições irreversíveis no desenvolvimento das plantas, mesmo com posterior aumento no suprimento de P para níveis adequados [4]. Neste sentido, tem-se observado respostas positivas da adubação fosfatada na cultura do girassol [5][6][7].…”
Section: Introductionunclassified
“…The lack of P in plants, especially at the beginning of the vegetative cycle, results in lower growth, delay in flowering, less filling of the achenes, and lower oil content [20,21]. Although previous studies have already demonstrated the productive behavior of sunflower and P application rates [22][23][24][25], few studies have been published conducted in semiarid regions, especially for the Brazilian semiarid region. Nutrient supply based on recommendations for humid or semi-humid regions should not be extrapolated to dry conditions because, in addition to environmental conditions, the cultivation system in the semiarid region is extremely peculiar [26].…”
Section: Introductionmentioning
confidence: 99%